The evolution of green leases: towards inter-organizational environmental governance - Janda, K; Bright, S; Patrick, J; Wilkinson, S; Dixon, T (Routledge, 2016)
Improving the environmental performance of non-domestic buildings is a complex and ‘wicked’ problem due to conflicting interests and incentives. This is particularly challenging in tenanted spaces, where landlord and tenant interactions are regulated through leases that traditionally ignore environmental considerations. ‘Green leasing’ is conceptualized as a form of ‘middle-out’ inter-organizational environmental governance that operates between organizations, alongside other drivers. This paper investigates how leases are evolving to become ‘greener’ in the UK and Australia, providing evidence from five varied sources on: (1) UK office and retail leases, (2) UK retail sector energy management, (3) a major UK retailer case study; (4) office leasing in Sydney, and (5) expert interviews on Australian retail leases. With some exceptions, the evidence reveals an increasing trend towards green leases in prime offices in both countries, but not in retail or sub-prime offices. Generally introduced by landlords, adopted green leases contain a variety of ambitions and levels of enforcement. As an evolving form of private–private environmental governance, green leases form a valuable framework for further tenant–landlord cooperation within properties and across portfolios. This increased cohesion could create new opportunities for polycentric governance, particularly at the interface of cities and the property industry.